Using Data Sciences for Analyzing Residential Electricity Consumption in Marginalized Mexican Municipalities - Ortiz-Guerrero, Natalie; Almanza-Ortega, Nelva N.; Pérez-Ortega, Joaquín; Santos-González, Iris (International Journal of Combinatorial Optimization Problems and Informatics, 2025)
In Mexico, the municipal marginalization index is used as a fundamental tool for planning and formulating public policies aimed at improving the socioeconomic conditions of the population. However, one of the limitations of this index is its exclusion of residential electricity consumption. In this regard, the present study explores the relationship between electricity consumption and the marginalization index. The research was conducted following the methodological framework of Data Science. As a result, geographic areas that cover municipalities with similar levels of residential electricity consumption were identified and characterized. It is noteworthy to mention that an inverse correlation was found between such consumption and marginalization index. Finally, these contributions could improve decision-making processes in public policies aimed at reducing economic and social inequalities, thus promoting more equitable development of the most lagging municipalities. Smart citations: https://scite.ai/reports/10.61467/2007.1558.2025.v16i4.942